SAT0400 Influence of Multiple Symptom Domains on Disease Impact in Patients Attending a Multidisciplinary Fibromyalgia Clinic. (23rd January 2014) - Garrood, T.; Medley, S.; Ferguson, A.; Keeling, D.; Duffort, P.; Irving, K.
Abstract : Background: Patients with fibromyalgia (FM) have a high prevalence of non-musculoskeletal symptoms including fatigue, psychological comorbidites and other somatic symptoms. Pharmacolgical therapy is widely used to treat pain, but a more holistic approach to treatment is not available to many FM patients despite the recommendation for physical and psychological therapy in published European guidelines. We have established a multidisciplinary clinic in which patients are assessed by a rheumatologist, psychologist and physiotherapist and provided with a comprehensive management plan with recommendations for pharmacological, physical and psychological therapy as appropriate. Objectives: The aim of this study was to investigate the impact of multiple symptom domains on overall disease impact and to determine the prevalence of psychological co-morbidities in our patient population. Methods: Patients meeting the 2010 preliminary American College of Rheumatology diagnostic criteria 1 and/or 1990 classification criteria for FM were asked to complete questionnaires including assessment of anxiety (GAD7), depression (PHQ9), fatigue (FACIT-fatigue), pain (visual analogue scale (VAS) and widespread pain index (WPI)) and the revised Fibromyalgia Impact Questionnaire (rFIQ) which is a validated tool for the assessment of overall disease impact 2 . The tender point count (TPC) was assessed by a physician who also recorded the symptom severity score (SSS). Correlation between variables was assessed by calculating the Pearson correlation coefficient. Significance was set at p<0.05. Data was analysed using SPSS statistical analysis software. Results: Data was available for 158 patients; of these 97% met the diagnostic criteria and 73% met the classification criteria for fibromyalgia. The mean age was 45 and 90% were female. 59% of patients scored in the moderate to severe range for anxiety on the GAD7 and 80% scored in the moderate to severe range for depression on the PHQ9. All variables except TPC (pain VAS, WPI, GAD7, PHQ9, FACIT-fatigue, SSS) correlated significantly with total rFIQ. Multivariate regression analysis identified pain VAS, FACIT-fatigue and PHQ15 scores as independently associated with rFIQ. Conclusions: In a population of FM patients referred to a specialist clinic pain, fatigue and the degree of somatic symptoms are independently associated with impact on patients' quality of life. In addition there is very high prevalence of depression and anxiety. Many of these patients have not previously been diagnosed with a psychological disorder and of those that have many have not received cognitive behavioural therapy (CBT)-based treatment. Recent metaanalysis data has suggested that pharmacological therapy for FM may be of limited benefit and greater effect sizes are seen with CBT and physical therapy. These data support the view that a multidisciplinary approach which addresses multiple symptom domains is essential to the effective management of patients with FM. References: Wolfe F, Clauw DJ, Fitzcharles MA, et al . The American College of Rheumatology preliminary diagnostic criteria for fibromyalgia and measurement of symptom severity. Arthritis Care Res 2010;62 :600-610. Bennett RM, Friend R, Jones KD, et al . The Revised Fibromyalgia Impact Questionnaire (FIQR): validation and psychometric properties. Arthritis Res Ther 2009;11 :R120 Disclosure of Interest: None Declared